Biosorption Of Copper And Zinc Using Waste Aspergillus Niger Biomass - J. M. Modak; K. A. Natarajan; B. Saha (Society for Mining, Metallurgy & Exploration, 1997)
Nonliving waste biomass consisting of Aspergillus niger attached to wheat bran was used as a biosorbent for the removal of copper and zinc from aqueous solutions. Copper and zinc uptake by the biomass obeyed Langmuir isotherms. The binding capacity of the biomass for copper was found to be higher than that for zinc. The metal uptake, expressed in milligrams per grain of biomass, was found to be a function of: •the initial metal concentration (with the uptake decreasing with increasing initial concentration), •the biomass loading (with the uptake decreasing with increasing biomass loading) and •pH (with the uptake increasing with increasing pH in the range of L5 and 6.0). The metal uptake was significantly affected in the presence of a co-ion. The uptake of copper by the biomass decreased in the presence of zinc and vice versa. The decrease in metal uptake was dependent on the concentrations of metals in the two-component aqueous solutions. The effect of copper on zinc uptake was more pronounced than the effect of zinc on copper uptake.